Phenylboronic acid conjugated multifunctional nanogels with 131I-labeling for targeted SPECT imaging and radiotherapy of breast adenocarcinoma - Kong, Lingdan; Zhu, Jingyi; Su, Hongxing; Zhao, Lingzhou; Lu, Yi; Zhu, Meilin; Sun, Wenjie (Frontiers in Bioengineering and Biotechnology, 2022)
We report a new 131I-labeling functional platform for targeted single-photon emission computed tomography (SPECT) imaging and radiotherapy of breast adenocarcinoma. In this study, polyethyleneimine (PEI) based nanogels (P.NH2 NGs) were prepared by water/oil polymerization, modified with targeted agent phenylboronic acid (PBA), and labelled with radionuclide 131I. The NGs platform without 131I-labeling own a spherical structure, uniform size distribution, and good cell viability. After131I-labeling, the obtained 131I-PBA-PHP NGs displayed much higher cellular uptake than the non-targeted NGs due to the good softness and fluidity of NGs and the PBA targeting. The in vivo results demonstrated that 131I-PBA-PHP NGs could specifically target breast cancer cells and efficiently aggregate into xenograft breast adenocarcinoma for tumor SPECT imaging and specific radiotherapy. The developed 131I-labeling NGs may be used as a promising platform for efficient radioactive theranostic nanoplatform of tumor.